1991
DOI: 10.1111/j.1365-2591.1991.tb00116.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects on the dental pulp of a composite resin and two dentine bonding agents and associated bacterial microleakage

Abstract: The pulpal reaction associated with a composite resin alone and composite resin used in conjunction with two dentine bonding agents was studied. Class V cavities were prepared on the labial surfaces of the canine teeth of 18 male ferrets. After acid etching of the enamel margins, the cavities were restored with either a composite resin alone or in combination with one of two dentine bonding agents, Scotchbond and Gluma. One cavity in each animal was filled with Kalzinol as a control. The animals were killed af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 19 publications
0
8
0
2
Order By: Relevance
“…Specifically, Bis-GMA and UDMA reduced the growth rate of Streptococcus sobrinus and Lactobacillus acidophilus, while TEGDMA stimulated growth rate and biomass production. The relevance of these findings in terms of biodegradation is very important, since bacteria have been shown to colonize crevices at the interface of composite restorations and the natural tooth (Lundin et al, 1990;Grieve et al, 1991). This has been postulated to lead to discoloration and failure of the resin composite.…”
Section: (Iv) Effects Of Degradation Products On Cells and Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, Bis-GMA and UDMA reduced the growth rate of Streptococcus sobrinus and Lactobacillus acidophilus, while TEGDMA stimulated growth rate and biomass production. The relevance of these findings in terms of biodegradation is very important, since bacteria have been shown to colonize crevices at the interface of composite restorations and the natural tooth (Lundin et al, 1990;Grieve et al, 1991). This has been postulated to lead to discoloration and failure of the resin composite.…”
Section: (Iv) Effects Of Degradation Products On Cells and Bacteriamentioning
confidence: 99%
“…While the degradation of restorative dental materials which contain polymeric resins has been of interest for some time (Truong and Tyas, 1988;Taylor et al, 1989;Winkler et al, 1991;de Gee et al, 1996), most of this work has concentrated on the loss of mechanical function and physical structure (Condon and Ferracane, 1997), rather than on the chemical breakdown and the subsequent effects of this chemical breakdown on the sur-rounding biological elements (specifically, salivary and tissue components interfacing with the materials). The vast majority of studies which have examined the effects of polymer resin components (derived from restorative composites) (Ferracane et al, 1998) on biological function (i.e., bacteria and cells residing in the soft tissue of the oral cavity) have been concerned with leached monomer components and not biodegradation products derived as a result of exposure to cells and biological fluids (0rstavik and Hensten-Pettersen, 1978;Grieve et al, 1991;Tanaka et al, 1991;Jontell et al, 1995;Hansel et al, 1998;Mohsen et al, 1998). It was only in the early part of the 1990s that serious consideration was given to the possibility that enzymes, associated with saliva and oral tissues, may be involved in catalyzing chemical reactions which could degrade dental resin systems Munksgaard and Freund, 1990;Larsen and Munksgaard, 1991;Larsen et al, 1992), although others (0ysaed et al., 1988) had previously suggested that composite resins were prone to oxidation and could release formaldehyde as a by-product.…”
Section: (I) Introductionmentioning
confidence: 99%
“…Although there are many researches evaluating the biocompatibility of restorative materials, it is not sufficient to investigate the effect of materials on cell viability. Such studies should be supported with different parameters, so that the accuracy of the results increased [1][2][3][4][5]. For this purpose, we compared the probable effect of different dental composites on GFBCs, CNCs and DPSCs.…”
Section: Discussionmentioning
confidence: 99%
“…The composites used in dentistry consist of different organic molecules. The organic matrix is based on methacrylate chemistry, with the most popular monomers being crosslinking dimethacrylates, for example; bisphenol A-glycidyl methacrylate (Bis-GMA), triethylene glycol dimethacrylate (TEGDMA), urethane dimethacrylate (UDMA, hydroxyethyl methacrylate (HEMA) or decanediol dimethacrylate (D3MA) [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…It has been taught that when a restoration is placed, the presence and severity of pulpal inflammation is related to the level of bacterial microleakage around the restoration. [38][39][40][41] Thus it would be logical to think that leaving dentine caries which is heavily infected would result in similarly severe pul-PRACTICE restorative dentistry tion of new dental materials, demand further research into this subject, particularly where older more compromised teeth are concerned. The pulp therefore has not had any opportunity to mount its protective reaction and the presence of bacteria and their by-products are in contact with dentine whose tubules are potentially patent and pulp vulnerable.…”
Section: Stepwise Excavationmentioning
confidence: 99%